The Roles of Teacher in Facilitating English Learning for the First Year Students with Low Basic English Proficiency in Integrated Skills at SMP IT Modern Al-Aksi Lonrong - Ahmad Sukri; Abdullah; Yunitari Mustikawati (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study explores the teacher’s role in facilitating the development of integrated English language skills: listening, speaking, reading, and writing among first-year junior high school students with low basic proficiency. Employing qualitative and quantitative methods, data were collected through teacher interviews, student Interview, classroom observations, and student questionnaires. Findings indicate that the teacher played a pivotal role in scaffolding each language skill through strategies such as multimedia use, collaborative learning, contextual teaching, and differentiated instruction. While students responded positively to engaging learning environments and appreciated support in speaking and vocabulary development, they continued to face challenges in listening comprehension, reading analysis, and grammar-based writing tasks. Integrated skills instruction, which mirrors real-life language use, was consistently applied by the teacher to enhance comprehension, motivation, and learner autonomy. Overall, students perceived the teacher’s role as effective, though more targeted support was needed for grammar instruction and comprehension-based activities. Future research should examine the long-term effects of integrated skills instruction and explore the role of technology and teacher scaffolding in supporting low-proficiency students.